2021
DOI: 10.3390/ijerph18063305
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Replicating a Randomized Control Trial Evaluation of an App-Based Sexual Health Program

Abstract: This study presents findings from a randomized control trial replication evaluation of Pulse, an app-based pregnancy prevention program implemented with Black and Latinx women aged 18–20, a population with high rates of unplanned pregnancy. We used social media advertisements to enroll 1013 women online across the U.S. and automatically randomized participants to either the Pulse reproductive health app or a general health control app, stratifying by age and race/Latinx ethnicity. Participants received reminde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
5
1
Order By: Relevance
“…The results of this study are different from the previous studies which stated that education using application media can increase knowledge [16], [17], [18], [19], [20]. However, there were several differences, for example, in the research of Vanestanagh et al, which found smartphone-based education can increase knowledge about reproductive health.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study are different from the previous studies which stated that education using application media can increase knowledge [16], [17], [18], [19], [20]. However, there were several differences, for example, in the research of Vanestanagh et al, which found smartphone-based education can increase knowledge about reproductive health.…”
Section: Discussioncontrasting
confidence: 99%
“…The choice of using media applications or mobile phone interventions is also considering that reproductive health and adolescent sexuality education services have not been routinely provided in public health services [22]. In the study of Manlove et al, giving a pulse reproductive health application could also increase adolescent self-confidence in using contraception [18].…”
Section: Discussionmentioning
confidence: 99%
“…84 There are also innovative approaches to leverage other types of technologies, beyond telehealth, to address the reproductive 85 and mental health 86 needs of adolescents, but there is a paucity of research in this area that pertains specifically to EPT. 87…”
Section: Implications For Addressing Social Determinants In Shaping E...mentioning
confidence: 99%
“…84 There are also innovative approaches to leverage other types of technologies, beyond telehealth, to address the reproductive 85 and mental health 86 needs of adolescents, but there is a paucity of research in this area that pertains specifically to EPT. 87 Despite these efforts, there is a need for increasing the number and strength of community partnerships across the public and private sectors. For instance, summer internship programs, such as for EPT, provide job training, offer linkages to health screenings and care, as well as parenting and lifeskills training and support.…”
Section: Implications For Addressing Social Determinants In Shaping E...mentioning
confidence: 99%
“…These social and structural barriers have impeded STI prevention in SSA [56][57][58][59][60]. Digital health innovations for training SRH care providers can link adolescents and young people to needed services and allow for the social monitoring of SRH services for adolescents and young people [61,62].…”
Section: Principal Findingsmentioning
confidence: 99%